Characteristics and Applications of Bionanosilica from Betung Bamboo Leaves - Esti Prihatini; Dwi Laksono, Gilang; Khairunissa, Dhiya; Rahayu, Istie; Ismail, Rohmat (Journal of Engineering, Technology, and Applied Science (JETAS), 2024)
Nanoparticles are materials that are currently widely used in research due to their novelty and the growing number of suitable applications. Silica nanoparticles can be produced by synthesizing using several methods such as melting, coprecipitation, sol-gel, and ultrasonication. The aim of this study is to determine the most appropriate synthesis method for the production of SiO₂ nanoparticles to optimize the quality of physical properties of fast-growing wood. The synthesis of SiO2 nanoparticles used in this study utilized three different methods: acid isolation method (F1), sol-gel method (F2), and reflux method (F3). Characterization of SiO2-NPs was performed using particle size analyzer (PSA), X-ray diffraction analysis (XRD), and Fourier transform infrared spectroscopy (FTIR). The results of PSA analysis showed that the acid isolation method produced the smallest SiO2 particle size compared to the sol-gel and reflux methods. The zeta pontential value in each method shows that the particles produced are unstable because the potential zeta value produced is around -10 mV to -30 mV. The results of FTIR and XRD analysis show that the synthesized material is a SiO₂ compound with a cristobalite phase. Application of the material on jabon wood through impregnation showed an improvement in physical properties, including an increase in WPG, density, and BE, especially in the sol-gel method (F2).